Socialization Strategy for the Implementation of HIRADC for Workers in the Operation of Dust Collectors in Mining Areas - Hanif, Yafi Nur; Suhendar, Suhendar; Wardoyo , Siswo (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to examine workplace hazards and assess occupational risks associated with dust collector operations in mining environments, while formulating an effective socialization strategy to enhance workers’ understanding of HIRADC implementation. The research method involves identifying potential hazards, evaluating risk levels, and determining appropriate control measures based on real field activities. Findings indicate two primary hazards: the possibility of electrical short circuits during equipment operation and dust exposure during filter cleaning, both categorized as moderate to high risks. The proposed socialization approach includes interactive training sessions, visible hazard information postings at the worksite, and regular evaluations of control effectiveness. In conclusion, continuous HIRADC socialization can improve workers' safety awareness, reduce accident and health risks, and strengthen the overall safety culture within the mining industry. Validation of the research findings was carried out by a certified Occupational Safety and Health (OSH) expert, confirming that the proposed socialization and control strategies align with practical safety standards and effectively support risk reduction in mining operations.